Writing from dance training and creation: systematization for university academic innovation - Herra Castro, Natalia (2020)
This academic essay presents to readers a proposal for a curricular innovation in university formation in dance, based on the systematization of artistic creation experiences and university training processes, with the possibility of impacting on the specialized field of contemporary dance, as well as in the visibility of the contribution of this artistic-scenic discipline to the social and cultural development of the country. This essay begins with the configuration of the concept of systematization of experiences, in a multidimensional way, the relationships between the current dynamics of contemporary art with innovation in the curriculum and university teaching, in the field of professional training in contemporary dance. In addition, the ethical imperative of decolonizing knowledge in the art of dance, from the university academy, based on the reflexive praxis of practical knowledge of dance art and its teaching / learning, from a critical perspective of research in, from and for contemporary dance. To conclude with proposals for the systematization of university professional training and artistic creation experiences that impact in the specialized field of dance, in Costa Rican society and the construction of cooperation and art development networks, at national and global level.